Peran Manajemen Pendidikan Dalam Pembentukan Karakter Akhlak Mulia Peserta Didik SMP - Dinda Amalia; Ai Surtika Dewi; Arif Hidayat (Journal on Education, 2023)
This research is motivated by the persistence of juvenile delinquency at the first school age due to the weakness of inculcating noble character values through the school curriculum. The research was conducted to obtain an overview of the role of management in shaping the noble character of students which was studied based on planning, organizing, implementing, supervising, inhibiting factors and improvement efforts. This study used a descriptive method with a qualitative approach through interviews, observation and documentation studies. The results of the study show that the role of education management in the formation of the noble character of students can provide meaning to the concept of management of educational and learning activities through planning, organizing, implementing, and supervising, however, to achieve the expected goals, there are still obstacles to the availability of infrastructure, ability and sincerity. educators, and the lack of school cooperation with related external parties. Thus, achieving this character requires the support of school resources, the involvement of the family, community and local government in carrying out sustainable noble character development